ANALISIS SUPPORT VECTOR REGRESSION (SVR) DENGAN KERNEL RADIAL BASIS FUNCTION (RBF) UNTUK MEMPREDIKSI LAJU INFLASI DI INDONESIA - Isnaeni R; Sudarmin Sudarmin; Zulkifli Rais (VARIANSI: Journal of Statistics and Its application on Teaching and Research, 2022)
Inflation is one indicator that affects the economic growth of a country. As a developing country, Indonesia has an unstable inflation rate every year. Therefore, it is necessary to predict the inflation rate in the future to be useful for formulating future economic policies. SVR is a Support Vector Machine (SVM) development for regression cases. In the SVR method, the RBF kernel is used as an aid in solving non-linear problems, the Min-Max Normalization method for data normalization, distribution of training data and testing data, selecting the best model with Grid Search Optimization, then forecasting using the model obtained with parameter = 0,1, C = 1, and = 3. The forecasting results obtained were evaluated by looking at the RMSE value, the test value obtained was RMSE of 0.0020, which means the model's ability to follow the data pattern well